Cameroon : Report on the Observance of Standards and Codes; Fiscal Transparency Module. (IMF Staff Country Reports; Country Report ;, 2010)
The report presents a reassessment of fiscal transparency practices in the Republic of Cameroon, in comparison with the principles of the IMF Code of Good Practices on Fiscal Transparency. It is the follow-up to a pilot report prepared by the IMF on transparency in fiscal management. The first part describes current fiscal transparency practices in Cameroon. The second component is the IMF staff commentary on fiscal transparency in the Republic of Cameroon. This report also contains an assessment of transparency in natural resource revenue management.